PENGARUH PEMBERIAN INFORMASI KESEHATAN BERBASIS APLIKASI WHATSAPP TERHADAP REMAJA DI SEKOLAH MENENGAH ATAS - ari rahmat aziz; Cecep Eli Kosasih; Mamat Lukman (Jurnal Ilmu Keperawatan, 2019)
ABSTRACT Tobacco consumption is the highest cause of illness and death in the world. Most smokers have smoked when their teens. At present, teenagers get used to using the internet and social media. The number of social media users whatsapp reached 1 billion users worldwide.This situation makes social media whatsapp a potential way to help teenagers stop smoking. The purpose of this studied to analyze the effect of giving health information based on whatsapp application to adolescent knowledge. This research used quasi experiment method with control group. Sample technique used simple random sampling. The intervention group was conducted at senior high school A and control group in senior high school B. The total sample was 76 students with 38 intervention groups and 38 control groups. Measurement of knowledge used questionnaires. In the intervention group were given text messages, motivational interviews and pictures for 4 weeks. In the control group were given health information in the form of danger smoking poster and smoking ban in school Mading. Test analysis used unpaired t test and Man-Whitney with significance <0.05. The result of bivariate analysis showed that there was significant difference of mean score of knowledge in the intervention group p = 0.00 before and after intervention. In the control group, there was a decrease in mean knowledge score (p = 0.015) before and after the study. There was a significant difference in mean knowledge between the intervention and the control group after intervention (p = 0.000). The provision of health-based social media information whatsapp significantly affects the knowledge of adolescent smokers. School health nurses and health care providers can apply the results of this study to help teenagers quit smoking. Application of research results will provide an alternative to heath education in adolescents in addition to the provision of face-to-face interventions. Keywords: adolescence, health information, whatsapp